1992
DOI: 10.1002/jcp.1041510215
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Na, K‐ATPase activity of Madin‐Darby Canine Kidney cells in defined medium by Prostaglandin E1 and 8‐bromocyclic AMP

Abstract: The role of PGE1 in regulating the activity of the Na+, K(+)-ATPase in Madin Darby Canine Kidney (MDCK) cells has been examined. PGE1 increased the initial rate of ouabain-sensitive Rb+ uptake by MDCK cells, a process that continued to occur over a 5-day period. The increase in the initial rate of ouabain-sensitive Rb+ uptake in MDCK cells treated with PGE1 could be explained by a 1.6-fold increase in the Vmax for ouabain-sensitive Rb+ uptake. The increase in the Vmax for ouabain-sensitive Rb+ uptake observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
(39 reference statements)
1
28
0
Order By: Relevance
“…PGE 1 , a growth supplement in this medium, stimulates transport via the Na, K-ATPase, as well as growth [16,17]. Our investigations with variant MDCK cells indicate that the stimulatory effects of PGE 1 on the Na, K-ATPase occur by means of signaling pathways which are distinct from those responsible for the growth stimulatory effect of PGE 1 [1,17]. Indeed PGE 1 independent variants (PGE 1 Ind) of MDCK cells retain the stimulatory effect of PGE 1 on the Na, K-ATPase, while having lost the stimulatory effect of PGE 1 on growth [1,18,19].…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…PGE 1 , a growth supplement in this medium, stimulates transport via the Na, K-ATPase, as well as growth [16,17]. Our investigations with variant MDCK cells indicate that the stimulatory effects of PGE 1 on the Na, K-ATPase occur by means of signaling pathways which are distinct from those responsible for the growth stimulatory effect of PGE 1 [1,17]. Indeed PGE 1 independent variants (PGE 1 Ind) of MDCK cells retain the stimulatory effect of PGE 1 on the Na, K-ATPase, while having lost the stimulatory effect of PGE 1 on growth [1,18,19].…”
Section: Introductionmentioning
confidence: 68%
“…Our investigations with variant MDCK cells indicate that the stimulatory effects of PGE 1 on the Na, K-ATPase occur by means of signaling pathways which are distinct from those responsible for the growth stimulatory effect of PGE 1 [1,17]. Indeed PGE 1 independent variants (PGE 1 Ind) of MDCK cells retain the stimulatory effect of PGE 1 on the Na, K-ATPase, while having lost the stimulatory effect of PGE 1 on growth [1,18,19]. The PGE 1 Ind MDCK cells had elevated intracellular cAMP levels, which can be attributed to their decreased cAMP phosphodiesterase activity [18].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Previously, we reported that PGE 1 , and 8-Bromocyclic AMP (8Br-cAMP) cause an increase in the Na,K-ATPase activity of MDCK cells [19], which was associated with an increase in the level of the Na,K-ATPase in this cell type [4]. The Na,K-ATPase is a protein which is composed of an α subunit with catalytic activity, as well as a β subunit, which facilitates the integration of the protein into the plasma membrane [20].…”
Section: Introductionmentioning
confidence: 99%